Stone Expulsion Rates with Medical Expulsion Therapy vs Expectant Management in 5 to 7 mm Distal Ureteric Stones: A Prospective Comparative Study - Rayamajhi, Bikash Bahadur; Shrivastav, Abhishek; Thapa, Narayan; Basukala, Bikram; Shrestha, Sajan (Journal of Society of Surgeons of Nepal, 2025)
Introduction: Distal ureteric stones measuring 5–7 mm pose a clinical dilemma as they may pass spontaneously but often cause severe colic and complications. Medical Expulsion Therapy (MET) with alpha-blockers, such as tamsulosin, has been proposed to facilitate passage, but its true benefit over expectant management (EM) remains debated. This study aimed to compare stone expulsion rates, time to passage, and emergency department (ED) visits between MET and EM.Methods: A prospective observational study was conducted at Shree Birendra Hospital, Kathmandu, Nepal, from June 2024 to June 2025. Adult patients (18–65 years) with a single distal ureteric stone (5–7 mm) confirmed by NCCT-KUB were included. Exclusion criteria were bilateral/multiple stones, anatomical abnormalities, prior ureteric surgery, significant hydronephrosis, pregnancy, single functioning kidney, active UTI and deranged renal function. Patients received either MET with tamsulosin 0.4 mg daily for 4 weeks plus analgesics and hydration (Group A, n=50) or EM with hydration and analgesics alone (Group B, n=50). Outcomes assessed were spontaneous expulsion of stone, time to passage, and ED visits for severe colic.Results: Spontaneous expulsion was observed in 82% of patients in the MET group versus 74% in the EM group (p=0.334). Median expulsion time did not differ significantly between groups, with most stones passing within two weeks. Notably, ED visits were significantly lower in the MET group (12% vs 30%, p=0.027).Conclusions: While MET did not significantly improve stone expulsion rates or passage time compared to EM, it significantly reduced ED visits, suggesting a role in symptom control. Larger randomized studies are needed to define the patient subgroup most likely to benefit.